Thermodynamic analysis of agonist and antagonist binding to the chicken brain melatonin receptor. - Chong, N. W. (1994)
1. The binding of 2-[125I]-iodomelatonin to chicken brain membranes, and the inhibition of binding by melatonin, N-acetyltryptamine and luzindole, were examined at temperatures between 4 degrees C and 37 degrees C. 2. At all temperatures studied, the binding affinity (Kd or Ki) for 2-[125I]-iodomelatonin, melatonin (both agonists) and, to a lesser extent, N-acetyltryptamine (a partial agonist) was reduced by inclusion of guanosine triphosphate (GTP, 1 mM) in the assay. GTP did not affect the Ki for luzindole, a melatonin receptor antagonist. 3. The maximal density of binding sites (Bmax) was not affected by temperature but the Kd showed a peak at 21 degrees C with lower values at both higher and lower temperatures giving curvilinear van't Hoff plots (lnKA vs l/temperature). 4. Derived changes in entropy (delta S degree) and enthalpy (delta H degree) of binding for all of the melatonin ligands decreased as temperature increased. 5. The affinity, and thus the free energy of binding, delta G degree, of these ligands at the melatonin receptor have identical values at several temperatures yet at these temperatures delta S degree and delta H degree were very different, implying that more than one intermolecular force must be involved in the binding of ligand and receptor. 6. Conceivably, the large positive delta S degree observed at low temperatures, perhaps as a result of hydrophobic interactions, is compensated by a corresponding, but opposite, change in enthalpy at higher temperatures. However, it is not clear what type of binding force(s) would show such a temperature-dependence. 7. These studies suggest that caution must be exercised in the molecular interpretation of derived measures of delta S degree and delta H degree obtained from direct measurements of delta G degree.